배 검은별무늬병 저항성 품종 ‘그린시스’ 육성 - 김윤경(Yoon-Kyeong Kim); 강삼석(Sam-Seok Kang); 원경호(Kyung-Ho Won); 신일섭(Il-Sheob Shin); 조광식(Kwang-Sik Cho); 마경복(Kyeong-Bok Ma); 김명수(Myung-Su Kim); 최장전(Jang-Jeon Choi); 최진호(Jin-Ho Choi) (Weon'ye gwahag gi'sulji, 2016)
To develop scab-resistant pear (Pyrus spp.) varieties with fruits that are as crisp and juicy as Asian pears, a cross was made between 'Whangkeumbae' and 'Bartlett' varieties (P. pyrifolia ${×}$ P. communis) at the Pear Research Institute of the National Institute of Horticultural & Herbal Science, Rural Development Administration, in 1994. Among the 285 seedlings, 'Greensis' was first selected in 2006 for its good eating quality and named in 2012 after regional adaptation tests in nine regions and ten experimental plots from 2007 to 2012. The tree showed a vigorous growth habit and semi-spreading characteristics, like 'Whangkeumbae'. The optimum fruit harvest date was also around Sept. 26 and fruit was round in shape and green in skin color at maturity. Average fruit weight was 470g, and the soluble solids content was $12.4^{°}Brix$. The flesh was very crisp and juicy, and had good eating quality. Its' leaf size was similar with 'Bartlett' and smaller than 'Whangkeumbae'. The average of full bloom date of 'Greensis' was determined as Apr. 26, which was six days later than 'Whangkeumbae' and similar with 'Bartlett'. S genotypes of 'Greensis' were identified as $S_4S_e$ by S-allele PCR product sequencing analysis. It seems that the $S_4$ allele was inherited from 'Whangkeumbae' and the Se allele from 'Bartlett'. 'Greensis' displayed strong resistance to scab disease caused by Venturia nashicola, similar to European pear cultivars like 'Beurre Hardy' and, 'Conference'. 'Greensis' was also highly resistant to black leaf spot (Alternaria kikuchiana) in the field '그린시스'는 아삭하고 과즙이 풍부한 동양배에 검은별무늬병(V. nashicola)에 저항성을 인자를 도입하기 위해 1994년 국립 원예특작과학원 배연구소에서 '황금배'와 'Bartlett'을 교배하였다. 285개 교배실생 중 식미감이 뛰어난 '그린시스'를 2006년에 1차 선발하고 2007년부터 2012년까지 5년간 9개 지역 10개소에서 지역적응성을 검토한 후 2012년 최종 선발하였다. '그린시스'의 성숙기는 9월 26일로 원형에 녹색 과피를 갖는 품종이다. 평균과중은 470g 내외, 당도는 $12.4^{°}Brix$이다. 과육은 아삭아삭하고 과즙이 풍부하여 식미가 좋다. '그린시스'의 엽 크기는 '황금배'보다 작고, 'Bartlett'과 유사하였다. 만개기는 4월 26일로 '황금배'보다 약 6일이 늦고, 'Bartlett'과 유사하였다. '그린시스'의 S allele 분석결과, $S_4S_e$로 확인되었는데 $S_4$ allele은 '황금배'로부터, $S_e$ allele은 'Bartlett'으로부터 유전되었다. '그린시스'는 검은별무늬병에 'Beurre Hardy', 'Conference' 등 서양배와 비슷한 수준의 저항성을 보였고, 검은무늬병(A. kikuchiana)에 포장저항성을 나타냈다.